Sectoral adjustment of employment: The impact of outsourcing and trade at the micro level - Peter Egger; Michael Pfaffermayr; Andrea Weber (Institute for Advanced Studies (IHS), 2003)
This paper analyzes the effects of trade and outsourcing on the transition probabilities of employment between sectors, using a dynamic multinomial logit framework with fixed effects. The data contain individual Austrian male workers over the period 1988-2001. Our results strongly support the view that international economic forces are important determinants of labor market turnover. Increases in imports, terms of trade and, especially, in the outsourcing share negatively affect the probability of staying in or changing into the manufacturing sector, even more so for industries with a comparative disadvantage.
Keywords: F16; J63; C23; C25; 330; labor market turnover; outsourcing; dynamic discrete choice; fixed effects panel estimation; Arbeitsmobilität; Sektorale Beschäftigungsstruktur; Strukturwandel; Internationaler Wettbewerb; Outsourcing; Schätzung; Österreich